Beyond Aristotelianism: al-Farabi on revelation, humans and animals in his on the Perfect State - Stark, Michael William (AUC Knowledge Fountain, 2014)
In modern times, Aristotelian influence on Islamicate philosophical writing is exaggerated. Al-Fārābī did more than just copy Aristotle, he was an original thinker, and he may have sourced aspects of his thought and writing style from the Qurʾān. Consideration of al-Fārābī’s biography, works and historical context demonstrates his disinclination to base his writings on those of Aristotle. Al-Fārābī’s thoughts in the key area of revelation in al-Madīna al-fāḍila demonstrate his departure from ancient Greek belief in this area, although his use of individual reasoning also shows clearly his occasional disagreement with Islamic doctrine. Differences and commonalities between animals and humans as written by al-Fārābī can be compared with Aristotle’s dissimilar thoughts on these matters, refuting the idea that al-Fārābī was simply an Aristotelian philosopher. Use of the religious term fiṭra in al-Madīna al-fāḍila is a microcosm of its writer’s propensity to include the terminology of revealed religion in this book.